Adsorção e dessorção de fosfato em solução aquosa utilizando novo compósito desenvolvido a partir de concreto aerado autoclavado com cimento branco - Kuhn, Daiane Cristine (2023)
Phosphate (PO4-3) adsorption from aqueous solutions in concrete-based construction waste represents a low-cost, non-toxic, and sustainable technique, minimizing environmental impacts and preventing health problems. In this work, the adsorption and desorption of PO4-3 from aqueous solutions using autoclaved aerated concrete (CA), white cement (CB), and autoclaved aerated concrete activated with white cement (CC) were evaluated, representing an innovative adsorbent. Textured, morphological, and physical-chemical characteristics were determined in the adsorbents. Subsequently, tests were carried out to obtain optimal conditions with statistical planning using the rotational central composite design (DCCR) method. Kinetic, equilibrium, and thermodynamic adsorption and desorption tests (25, 35, and 45 ºC) were performed based on the verified optimal conditions. Assays with phosphate adsorption and desorption cycles were conducted. For adsorption in a fixed bed column, the DCCR was carried out, varying the influent flow and the mass of the adsorbents. Activation modified some properties of the adsorbents, increasing roughness and irregularity on the CC surface. Furthermore, higher CaO contents were observed in CC (59.52%) compared to CA (9.91%), influencing adsorption. Adsorption efficiencies under optimal conditions in CA, CC, and CB resulted in 99.99, 99.99 and 96.60%, respectively. The PSO model better represented the adsorption for CA (0.29 mg g-1; pH 6.35). For CC (0.54 mg g-1; pH 6.53) and CB (54.68 mg g-1; pH 7.5) the PFO and PSO models better represented the adsorption. In the adsorption isotherms, the Freundlich model stood out for CA (9.10 mg g-1). The Langmuir and RedlichPeterson models better represented the adsorption in CC (3.90 mg g-1). For CB (59.53 mg g-1), the Redlich-Peterson, Freundlich, and Langmuir models excelled in adsorption. As for transfer kinetics, transfer resources for AC and CC were 0.19 and 0.39 mg g-1. Desorption isotherm tests revealed desorption capacities of 0.45 and 1.97 mg g-1 for CA and CC. No desorption was observed for CB. Adsorption (in CA, CC, and CB) and desorption (in CA and CC) showed spontaneous reactions of exothermic and endothermic nature. After the adsorption/desorption cycles, the adsorption efficiencies decreased for CA and CC. On the other hand, the desorption efficiency increased for CA and decreased for CC after the cycles. The proposed mechanisms for adsorption are related to adsorption on Fe and Al hydroxides and oxides, precipitation of calcium phosphates, and electrostatic attraction. The proposed desorption mechanisms are electrostatic repulsion and ion exchange for AC and DC. In the assays with the fixed bed column, the optimal conditions of influent flow and adsorbent mass were obtained for CA (8.44 g and 1.30 mL min-1), CC (5.00 g and 1.00 mL min-1) and CB (0.27 g and 3.50 mL min-1). The alternative adsorbents CA, CC, and CB were suitable for increasing the phosphate adsorption and desorption capacity.